EXPLORING THE ROLE OF STUDENTS’ FEEDBACK IN ENGLISH LANGUAGE ACQUISITION - Irawansyah; Ayuni; Alisya Pratiwi; Khoirunisa (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This study explores the role of feedback in English language acquisition among the students of English Education Study Program at Universitas Islam Negeri Raden Intan Lampung. Employing a mixed-methods research design with a qualitative emphasis, the research involved 30 fifth-semester students. Research instruments included questionnaires and in-depth interviews to analyze students' perceptions of various feedback aspects. Findings reveal significant feedback importance in improving language skills, motivation, and student confidence. Eighty percent of respondents agreed that feedback helps identify improvement areas, while 78% stated that constructive feedback can enhance learning motivation. The study uncovered student preferences for written (70%) and immediate (60%) feedback, with interpretation variations influenced by social and cultural contexts. Practical implications emphasize the need for flexible feedback strategies, personalization, and integration with educational technology to create inclusive and effective learning environments